1992
DOI: 10.1136/bjo.76.12.711
|View full text |Cite
|
Sign up to set email alerts
|

Acyclovir ointment plus topical betamethasone or placebo in first episode disciform keratitis.

Abstract: Thirty patients with first episode disciform keratitis and with no previous steroid exposure were randomly assigned to double blind treatment with 3% acyclovir ointment and 0O1% betamethasone (Betnesol) drops or acyclovir ointment and matching placebo. In the steroid group 14 of the 15 patients healed in a mean time of 21-8 days. In the placebo group eight of the 13 patients healed in a mean time of 34-5 days. The difference in mean healing time between the two groups was significant (p<005). The cumulative ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 9 publications
2
13
0
1
Order By: Relevance
“…In a double-masked randomised trial, Power et al have shown that the cumulative rate of healing was better and quicker in the steroid group (betamethasone 0.1%) when compared with the placebo group 70. However, it is not known how this affects the recurrence rate of active herpetic disease.…”
Section: Therapeutic Implications In the Management Of Anterior Segmementioning
confidence: 99%
“…In a double-masked randomised trial, Power et al have shown that the cumulative rate of healing was better and quicker in the steroid group (betamethasone 0.1%) when compared with the placebo group 70. However, it is not known how this affects the recurrence rate of active herpetic disease.…”
Section: Therapeutic Implications In the Management Of Anterior Segmementioning
confidence: 99%
“…Hasarı oluşturan asıl neden immün yanıt olduğu için, tedavinin asıl basamağını antiviral ilaçlardan ziyade immünsupresifler (topikal veya sistemik kortikosteroid) oluşturmaktadır. 36,37 Topikal kortikosteroidler keratitin süresini kısaltır ve stromal inflamasyonu azaltır. 37 Ancak topikal kortikosteroidlerin yoğun kullanımı aynı zamanda korneal ülser ve perforasyon riskini arttırarak istenmeyen sonuçlara neden olabilir.…”
Section: Discussionunclassified
“…Topical antivirals targeting viral replication and corticosteroids targeting immune-mediated mechanisms are standard treatments for HSK, 10; 26; 27; 114 but have associated risks. For example, corticosteroid use is associated with increased risks of developing glaucoma and cataracts.…”
Section: Future Directionmentioning
confidence: 99%